2022
DOI: 10.2147/opth.s363061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance and Surgeon Acceptability of a New Dual Mode Phacoemulsification System

Abstract: Purpose The purpose of this first in-human study was to evaluate the overall clinical performance of the VERITAS™ Vision System in patients scheduled to undergo cataract extraction and to confirm overall surgeon acceptability. Patients and methods This prospective, open-label multinational study included adults with cataracts scheduled for planned cataract extraction and posterior chamber IOL implantation. Standard small-incision phacoemulsification cataract surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Some reports did not provide a definition or report how acceptability was measured (Bazzurini et al, 2022; James et al, 2021). Some studies concluded that the intervention was acceptable; however, on review of reported methods and results, references are made to ‘satisfaction’ which is arguably a different construct (Allenson et al, 2021; Quesada et al, 2022). These inconsistencies in the published literature demonstrate why consistent use of a definition, such as that proposed by Sekhon et al (2017) would be preferable and important.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports did not provide a definition or report how acceptability was measured (Bazzurini et al, 2022; James et al, 2021). Some studies concluded that the intervention was acceptable; however, on review of reported methods and results, references are made to ‘satisfaction’ which is arguably a different construct (Allenson et al, 2021; Quesada et al, 2022). These inconsistencies in the published literature demonstrate why consistent use of a definition, such as that proposed by Sekhon et al (2017) would be preferable and important.…”
Section: Introductionmentioning
confidence: 99%